2021
DOI: 10.1002/j.2769-2795.2021.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided peripheral trunk block technique: A new approach gradually stepping onto the stage of clinical anesthesia

Abstract: In recent years, with the continuous development and validation of new visualization, the ultrasound‐guided peripheral trunk block becomes more mature and has a more extensive and broader implementation scope in clinical anesthesia. Based on this, we reviewed and summarized the literature on peripheral trunk nerve block include: paraspinal block, retrolaminar block, plane block of erect spinal muscle, transverse convex to pleural midpoint block, block of the trapezius muscle and anterior serratus muscle, anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 123 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…TEA is currently the most common method of pain control for patients undergoing major thoracic and abdominal surgery [ 11 , 48 , 49 ]. However, with the advancement of ultrasound equipment and concerns about neurological injury, more anesthesiologists are using nerve blocks for these patients [ 50 ]. Although several studies have demonstrated the efficacy of nerve blocks [ 4 , 39 , 40 ], the pain characteristics of patients undergoing PE repair are different from those of patients undergoing other major thoracic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…TEA is currently the most common method of pain control for patients undergoing major thoracic and abdominal surgery [ 11 , 48 , 49 ]. However, with the advancement of ultrasound equipment and concerns about neurological injury, more anesthesiologists are using nerve blocks for these patients [ 50 ]. Although several studies have demonstrated the efficacy of nerve blocks [ 4 , 39 , 40 ], the pain characteristics of patients undergoing PE repair are different from those of patients undergoing other major thoracic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…TEA is currently the most common method of pain control for patients undergoing major thoracic and abdominal surgery [11,42,43]. However, with the advancement of ultrasound equipment and concerns about neurological injury, more anesthesiologists are using nerve blocks for these patients [44]. Although several studies have demonstrated the e cacy of nerve blocks [4,33,34], the pain characteristics of patients undergoing PE repair are different from those of patients undergoing other major thoracic surgeries.…”
Section: Discussionmentioning
confidence: 99%